2023
DOI: 10.1186/s12876-023-02718-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral abnormalities in C57BL/6 mice with chronic ulcerative colitis induced by DSS

Abstract: Background Clinical epidemiological studies have found that some patients with ulcerative colitis (UC) are prone to mental disorders. DSS-induced acute and chronic UC models are often used to evaluate the efficacy of anti-UC drugs. However, whether DSS has an effect on mouse behavior has not been reported. Methods Acute and chronic UC models were induced by 3% DSS and 1.5% DSS, respectively. The bloody stool, the changes in the colon length, and hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The mice exhibited symptoms and pathological characteristics similar to those of chronic UC induced clinically after modeling. 48 After treatment with BBR and PDA@BBR NPs, the symptoms of DSS-induced ulcerative colitis were alleviated, and the pathological tissue examination also showed varying degrees of repair in colonic goblet cells and crypts, with reduced inflammatory cell infiltration. 49 Among these parameters, including changes in mouse body weight, DAI score, and colon length, it was found that PDA@BBR NPs had a more effective therapeutic effect on UC than BBR ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 96%
“…The mice exhibited symptoms and pathological characteristics similar to those of chronic UC induced clinically after modeling. 48 After treatment with BBR and PDA@BBR NPs, the symptoms of DSS-induced ulcerative colitis were alleviated, and the pathological tissue examination also showed varying degrees of repair in colonic goblet cells and crypts, with reduced inflammatory cell infiltration. 49 Among these parameters, including changes in mouse body weight, DAI score, and colon length, it was found that PDA@BBR NPs had a more effective therapeutic effect on UC than BBR ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 96%
“…After one week of adaptation, male C57BL/6 mice (6-8 weeks of age, 20±2 g) were randomly divided into four groups (n=5/group): control group, dextran sodium sulfate (DSS) group, DSS + sh-NC (negative control) group, and DSS + sh-ANGPT2 group. Mice in the DSS group were fed normally and given 3% DSS diluted in water for 7 days ( 8 ). Mice in the DSS + sh-ANGPT2 group received 3% DSS and were injected with adeno-associated virus (AAV) shRNA targeting ANGPT2 (sh-ANGPT2) into the tail vein at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Salvo et al modeled pediatric IBD by administering 2% DSS for 5 days at weaning (P21) as a model of a single acute period of inflammation (Salvo et al, 2020). Studies in adult rodents have utilised several rounds of DSS to emulate recurring cycles of inflammation and remission (Eichele and Kharbanda, 2017;Okayasu et al, 1990;Zhou et al, 2023). Therefore, we adapted a model in which DSS is administered in the drinking water repeatedly across early postnatal development starting at postnatal day 21 (P21) (Ruemmele and Turner, 2014).…”
Section: An Early-life Dss Model Of Pediatric Ibdmentioning
confidence: 99%
“…The widely-used dextran sodium sulfate (DSS)-induced colitis model damages the gut epithelial lining and mimics the gut inflammation and microbiota changes seen in human UC (Chassaing et al, 2014). Adult mice treated with DSS have increased anxiety (Nyuyki et al, 2018) and reduced sucrose preference, indicative of a depression endophenotype (Zhou et al, 2023). Additionally, active gut inflammation in adult mice led to recognition memory impairments in both acute (Emge et al, 2016) and chronic DSSinduced IBD models (Bercik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%